A Systematic Literature Review: PvK12 and PfK13 Gene Mutations as Markers of Resistance to Artemisin - Susiwati Susiwati; Chairil Anwar; Zen Hafy; Iche Andriyani Liberty (GLOBAL HEALTH SCIENCE GROUP, 2025)
P. falciparum and P. vivax are among the most dangerous types of plasmodium , as they cause morbidity and mortality. Long-term use of Anti-Malaria Drugs (OAM) causes resistance. The purpose of this study was to determine the mutation of the pvk12 and pfk13 genes as a marker of resistance to artemisinin . This study used a systematic review method that was compiled based on the Preferred Reporting Items for Systematic Reviews and Meta Analyzes (PRISMA). The article search used five databases, namely PubMed, Google Scholar, BMC, Portal Garuda and the National Library (Perpusnas) of Indonesia. The keywords and boolean operators used in the literature search were